Probing RbBr solvation in freestanding sub-2 nm water clusters. Issue 36 (8th September 2017) - Hautala, Lauri; Jänkälä, Kari; Mikkelä, Mikko-Heikki; Turunen, Paavo; Prisle, Nønne L.; Patanen, Minna; Tchaplyguine, Maxim; Huttula, Marko
Abstract : Core level photoelectron spectra of freestanding sub-2 nm RbBr-water clusters reveals increased ion pairing beyond 2 mol kg −1 concentration. Abstract : Concentration dependent solvation of RbBr in freestanding sub-2 nm water clusters was studied using core level photoelectron spectroscopy with synchrotron radiation. Spectral features recorded from dilute to saturated clusters indicate that either solvent shared or contact ion pairs are present in increasing amount when the concentration exceeds 2 mol kg −1 . For comparison, spectra from anhydrous RbBr clusters are also presented.